2003
DOI: 10.1002/path.1297
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant expression of p16INK4a and p14ARF in primary breast cancer and analysis of inactivation mechanisms

Abstract: The INK4a/ARF locus encodes two tumour suppressor proteins, p16INK4a and p14ARF, which act in the two main cell-cycle control pathways, p16-Rb and p14-p53 respectively. The present study examined the mRNA expression of these genes by reverse transcription-polymerase chain reaction (RT-PCR), and the inactivation mechanisms that alter these levels, in 100 primary breast carcinomas. Furthermore, the interdependence of these mechanisms was examined, since it has been reported that p14ARF is altered in most tumours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
58
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(62 citation statements)
references
References 44 publications
2
58
0
2
Order By: Relevance
“…31 In conclusion, the comparative analysis of p16 expression in breast carcinoma and fibroadenoma suggest a role for p16 in breast malignancy although promoter methylation, differently from others tumors, cannot be considered a marker of carcinogenesis. Because p16 point mutations were very rarely observed 6,8 and the protein is massively present in carcinoma epithelium, we propose that in breast cancer, similarly to non-small cell lung cancer, 32 p16 loss of function occurs by sequestration of the protein in the cytoplasm rather than by mutational or transcriptional inactivation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…31 In conclusion, the comparative analysis of p16 expression in breast carcinoma and fibroadenoma suggest a role for p16 in breast malignancy although promoter methylation, differently from others tumors, cannot be considered a marker of carcinogenesis. Because p16 point mutations were very rarely observed 6,8 and the protein is massively present in carcinoma epithelium, we propose that in breast cancer, similarly to non-small cell lung cancer, 32 p16 loss of function occurs by sequestration of the protein in the cytoplasm rather than by mutational or transcriptional inactivation.…”
Section: Discussionmentioning
confidence: 90%
“…Even though homozygous deletions of p16 are seen in 40 -60% of breast cancer cell lines, 6,7 neither homozygous deletions nor point mutations are observed frequently in primary breast carcinomas suggesting that these alterations might have been acquired in culture. 6,8 Similar to many other genes, p16 INK4a is commonly inactivated by hypermethylation of its CpG-rich promoter region. 9 -11 This important cancer-related modification has also been detected in breast carcinoma, although the reported prevalence of p16 promoter methylation in this tumor is discordant among different studies.…”
mentioning
confidence: 99%
“…The INK4A/ARF locus critically regulates both the p53 and Rb tumor suppressor pathways and frequently is disrupted in human breast cancers (28)(29)(30). To investigate the impact of Ink4a/Arf deficiency on mammary tumor onset and subsequent tumor escape, a null Ink4a/Arf allele that disrupts both the p16 Ink4a and p19 Arf tumor suppressors (31) was introduced into the MTB/TWNT model via the germline to generate cohorts of Ink4a/Arf +/+ , Ink4a/Arf +/-, and Ink4a/Arf -/-female mice.…”
Section: Markers Of Wnt Pathway Activation In Mammary Tissue and Tumorsmentioning
confidence: 99%
“…Recently, a number of investigators have shown that in addition to DNA, RNA is also present in the plasma of human subjects, particularly those with cancer (15)(16)(17)(18). The inherent lability of RNA has made these observations rather surprising.…”
mentioning
confidence: 99%